(untitled) (Journal of Engineering, 2023)
Many researchers have tackled the shear behavior of Reinforced Concrete (RC) beams by using different kinds of strengthening in the shear regions and steel fibers. In the current paper, the effect of multiple parameters, such as using one percentage of Steel Fibers (SF) with and without stirrups, without stirrups and steel fibers, on the shear behavior of RC beams, has been studied and compared by using Finite Element analysis (FE). Three-dimensional (3D) models of (RC) beams are developed and analyzed using ABAQUS commercial software. The models were validated by comparing their results with the experimental test. The total number of beams that were modeled for validation purposes was four. Extensive parametric analysis has been carried out on another twelve beams to explore the influence of specific parameters, such as using different strengths of concrete, different flexural reinforcement bars, and laminate in the shear regions. It is concluded from the results that when a different compressive strength was assigned to RC beams, a decrease by 31 of beam ultimate strength was recorded when using C25 concrete strength. On the other hand, an improvement of 29% was observed by assigning concrete compressive strength C50. As well as another decrease of 18 and 26 kN was observed when GFRP was used with beams that had stirrups and beams that had both stirrups and SF. However, the beams recorded a higher number for ductility with using GFRP. In addition, using laminate with the beam that had both stirrups and SF was not beneficial; hence, the failure load was increased by only 3%, particularly with the beam that had both stirrups and SFs